2010
DOI: 10.1152/ajpgi.00524.2009
|View full text |Cite
|
Sign up to set email alerts
|

Roles of prostaglandin E2-EP1 receptor signaling in regulation of gastric motor activity and emptying

Abstract: Majima M. Roles of prostaglandin E 2-EP1 receptor signaling in regulation of gastric motor activity and emptying. Am J Physiol Gastrointest Liver Physiol 299: G1078 -G1086, 2010. First published August 26, 2010 doi:10.1152/ajpgi.00524.2009.-It is widely accepted that the inhibition of gastric motor activity as well as the maintenance of gastric mucosal blood flow and mucous secretion are important for the homeostasis of the gastric mucosa. The present study was performed to ascertain whether or not endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…For example, it is reported that PGE2 contributes to suppression of gastric emptying induced by intragastric injection of a hyperosmolar NaCl solution in rats (Nishiyama et al ., 1992; Mizuguchi et al ., 2010). Intragastric injection of enprostil, a PGE2 derivative, also reduces gastric emptying of barium grains in rats (Sakurai et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is reported that PGE2 contributes to suppression of gastric emptying induced by intragastric injection of a hyperosmolar NaCl solution in rats (Nishiyama et al ., 1992; Mizuguchi et al ., 2010). Intragastric injection of enprostil, a PGE2 derivative, also reduces gastric emptying of barium grains in rats (Sakurai et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of EP receptors could still reduce IOP [18,19], but might induce gastro-intestinal effects. EP1 signaling has crucial roles in the suppression of myoelectrical activity of gastric smooth muscles and inhibition of gastric emptying, as well as induction of contractions in the small intestine [20]. The activation of EP1 receptor by latanoprost or travoprost, in the absence of FP receptor, might incur obvious gastro-intestinal adverse effects, including nausea and vomiting.…”
Section: Hypothesismentioning
confidence: 99%
“…Further, using selective ligands we have recently shown that in human airways, PGE 2 relaxes smooth muscle tone via the EP 4 receptor (Buckley et al ., 2011). Indeed, there has recently been a plethora of publications describing the actions of PGE 2 (Narumiya, 2009; Esaki et al ., 2010; Mizuguchi et al ., 2010; Aoki et al ., 2011; Hosono et al ., 2011). , thanks mainly to the excellent tools developed by Ono Pharma and the genetically modified mice produced by Professor Narumiya.…”
mentioning
confidence: 99%
“…Further, using selective ligands we have recently shown that in human airways, PGE2 relaxes smooth muscle tone via the EP4 receptor (Buckley et al, 2011). Indeed, there has recently been a plethora of publications describing the actions of PGE2 (Narumiya, 2009;Esaki et al, 2010;Mizuguchi et al, 2010;Aoki et al, 2011;Hosono et al, 2011)., thanks mainly to the excellent tools developed by Ono Pharma and the genetically modified mice produced by Professor Narumiya.Investigations of the role of the EP2 receptor in responses mediated by PGE2 have proved to be difficult due to the lack of a suitable EP2 receptor antagonist. A recent publication in the British Journal of Pharmacology by af Forselles et al (2011) describing in detail a new EP2 receptor antagonist would suggest that there is now a complete set of EP receptor ligands.…”
mentioning
confidence: 99%